2022
DOI: 10.1161/circulationaha.121.057480
|View full text |Cite
|
Sign up to set email alerts
|

ECG-Based Deep Learning and Clinical Risk Factors to Predict Atrial Fibrillation

Abstract: Background: Artificial intelligence (AI)-enabled analysis of 12-lead electrocardiograms (ECGs) may facilitate efficient estimation of incident atrial fibrillation (AF) risk. However, it remains unclear whether AI provides meaningful and generalizable improvement in predictive accuracy beyond clinical risk factors for AF. Methods: We trained a convolutional neural network ("ECG-AI") to infer 5-year incident AF risk using 12-lead ECGs in patients receivin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
89
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 146 publications
(106 citation statements)
references
References 40 publications
(78 reference statements)
1
89
0
Order By: Relevance
“…We previously observed that ECG-AI estimates for AF risk are largely influenced by the P wave, a period corresponding to atrial depolarization and repolarization. 7 Moreover, we have previously reported that both ECG-AI and clinical risk for AF are complementary. 7 Here, we extend these observations by identifying genetic signals that have been associated with P wave duration, 36 and documenting the distinct genetic profiles underlying risk estimates generated by ECG-AI and a clinical risk factor model.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We previously observed that ECG-AI estimates for AF risk are largely influenced by the P wave, a period corresponding to atrial depolarization and repolarization. 7 Moreover, we have previously reported that both ECG-AI and clinical risk for AF are complementary. 7 Here, we extend these observations by identifying genetic signals that have been associated with P wave duration, 36 and documenting the distinct genetic profiles underlying risk estimates generated by ECG-AI and a clinical risk factor model.…”
Section: Discussionmentioning
confidence: 99%
“…The development and validation of the ECG-AI model has previously been reported. 7 Briefly, we trained a convolutional neural network (CNN) to predict 5-year risk of AF using 12-lead ECGs in a longitudinal patient cohort derived from the MGB network. 11 ECG-AI uses an encoding and loss function that takes into account both time to event (i.e., AF) and missingness introduced by censoring (death or loss of follow-up) to estimate a 5-year survival probability of AF.…”
Section: Predicted Risk Of Afmentioning
confidence: 99%
See 2 more Smart Citations
“…Along with the continuous innovation of convolutional algorithms, from LeNet by Lecun et al ( 36 ) to ResNet by He et al ( 37 ), computer-aided decision making through imaging has become a hot topic in medical research, such as prediction of BMI by facial image features to predict BMI ( 38 ) and fundus images to predict diabetic retinopathy ( 39 ). In addition, the prevalence of electronic medical records and the establishment of large medical databases have also provided the basis for research on clinical problems, and the combination with machine learning has shown remarkable performance in predicting the occurrence and prognosis of diseases ( 40 , 41 ). Unfortunately, however, there is still a lack of research in the current field for our patient population.…”
Section: Discussionmentioning
confidence: 99%